Early Detection of goats infected with Lentivirus Small Ruminant virus by ELISA assay - Sardi, Silvia Inês; Torres, Julianna Alves; Brandão, Camila Fonseca Lopes; Tigre, Dellane Martins; Campos, Gubio Soares (Revista de Ciências Médicas e Biológicas, 2012)
<!--[if gte mso 9]> 800x600 <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false ES-AR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman","serif";} --> <!--[endif] --> Many established protocols are available to produce antigens for ELISA tests but expensive equipments, the purification methods or recombinant technologies are not always available to veterinary diagnostic laboratories. The aim of this work was to develop an alternative ELISA test to detect antibodies against Lentivirus Small Ruminant Virus (Caprine arthritis-encephalitis virus-CAEV) in goats, simple to elaborate with a low cost of production. The antigen was obtain from a whole cellular lysates of goat synovial membrane cells (GSMC) infected with CAEV and treated with SDS 0,1%. The whole-viral antigen was capable of detecting antibodies against several viral proteins including the p28 kDa (viral capsid), the p33 kDa, the p44 kDa (capsid precursors) and p97 kDa (transmembrane glycoprotein). The comparison with others assays as indirect immunofluorescence showed a high correlation with the ELISA results and the polimerasse chain reaction (PCR) demonstrated that most of the goat seropositives by ELISA, had proviral DNA in the milk cells. In conclusion, the viral antigen obtained from GSMC was simple to elaborate, low cost of production. The ELISA test was capable of detecting antibodies against CAEV, to detect early infection.